Breath Stable Isotope Analysis Serves as a Non-invasive Analytical Tool to Demonstrate Dietary Changes in Adolescent Students Over Time - Mancuso, Christy J.; Cornwall, Collette M.; Robinson, Swede; Valenzuela, Luciano O.; Ehleringer, James R. (Frontiers in Medicine, 2022)
Concern about adolescent diets, obesity, and the associated health risks have been growing in the United States. This inspired former First Lady Michelle Obama to spearhead the Healthy Hunger-Free Kids Act (HHFKA), which made changes to the national school lunch program by increasing servings of whole grains, fruits, and vegetables. Our study examined the variability of student carbohydrate sources throughout the day and before and after the implementation of HHFKA using a stable isotope dietary biomarker. This method uses carbon stable isotope values of exhaled CO2 breath (δ13Cbreath) and provides a quantitative, non-invasive measure. δ13Cbreath samples were collected throughout the day from students (n= 31) that attended a public high school in Salt Lake City, UT. δ13Cbreath measurements reflected the short-term carbohydrate inputs from the previous meal. Carbohydrate sources were not consistent throughout the day; most students had their lowest inputs of corn/sugar-based carbohydrates after lunch. We compared our results with an earlier study that had been conducted pre-HHFKA. After-lunch δ13Cbreath values decreased significantly between the two time points, suggesting an increase in whole grain, fruit, and vegetable carbohydrates in the lunch program. Our results demonstrated that δ13Cbreath measurements provide a valuable tool to examine carbohydrate sources in an individual’s diet throughout the day. We believe that this tool could be beneficial to studies examining the relationship between sugar sweetened beverages, added sugars, and refined carbohydrates and health outcomes like diabetes and obesity in both adolescent and adult populations.